Impact of HPV educational intervention on knowledge and vaccination intentions among Ukrainian migrant and refugee parents in Poland - Ganczak, Maria; Kalinowski, Paweł; Kowalska-Babiak, Marta; Nazrieva, Mufida; Nyankovskyy, Serhij; Edelstein, Michael (Frontiers in Public Health, 2025)
BackgroundDespite the availability of HPV vaccines, uptake remains low among Ukrainian adolescents. Educational interventions can enhance parents’ knowledge and intent regarding HPV vaccination.ObjectiveTo evaluate the effects of a prospective, culturally tailored, evidence-based HPV vaccine face-to-face educational intervention on knowledge and vaccine intent among Ukrainian migrant and refugee (UMR) parents in Poland, utilizing a pre-post design.MethodsA study was conducted among 178 UMR parents between February and July 2024. Using telephone calls, research staff recruited consecutive parents registered to the network of primary care clinics “Medyk” in Rzeszów, Poland. Eligible parents were those having children aged 9–17 years, who had not completed the HPV vaccination. They completed pre- and post-data on HPV knowledge and intent. Four female Ukrainian GPs were trained to deliver 9 group interventions (2 h each); this had to be changed to 27 individual 1-h sessions after an erroneous suspicion of HPV vaccine adverse effects, which spread out in the Ukrainian community and resulted in a recruiting crisis. Data were analyzed using McNemar’s test and multilevel regression analysis.ResultsThe majority of participants were female (84.3%) and aged >30 years (77.5%); 59.6% of UMR parents presented a low knowledge level (≤50%). Only 30.3% knew all possible routes of HPV transmission, and 39.9% knew male HPV-related neoplasms. The intervention significantly improved HPV knowledge by 63.4% (pre: 5.2, SD ± 2.1; post: 8.2, SD ± 1.7; p < 0.0001). Parents who attended individual education had lower pre-intervention scores but outperformed parents who participated in the group sessions in post-intervention knowledge. Ukrainian mothers and parents with higher SES showed a significant improvement in vaccine intent after the intervention, from 56.6 to 64.8%, p = 0.04, and from 55.3 to 73.9%, p = 0.046, respectively.ConclusionThe study finds that educational interventions for UMR parents can improve their understanding of HPV and support informed vaccination decisions for their children. The integration of specific approaches—such as culturally sensitive messaging, the utilization of trained Ukrainian presenters, and tailored health literacy strategies based on the community needs—may provide critical support for future implementation efforts.